2006
DOI: 10.1111/j.1528-1167.2006.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtemporal Hippocampectomy Preserving the Basal Temporal Language Area for Intractable Mesial Temporal Lobe Epilepsy: Preliminary Results

Abstract: Summary:Purpose: Decline in verbal memory as a surgical complication remains an unresolved problem in mesial temporal lobe epilepsy. Some areas in the temporal lobe associated with the language function, often including the basal temporal language area, have been removed or transected by conventional surgical procedures. The authors defined the basal temporal language area and removed only the epileptogenic zone with a subtemporal approach.Methods: The basal temporal language area was evaluated by using long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…The need to incise, resect, or retract the temporal or occipital lobes during surgery of the MTR is a controversial issue. 1,3,4,[8][9][10]12,13,15,20,26,27,29,30,33,[35][36][37][38][42][43][44][45][46][47][48]50,[57][58][59]67 This enclosed and extended localization near these highly significant structures renders the MTR a difficult surgical area in some respects. This location necessitates the least traumatic approach without the risk of injury to overlying…”
mentioning
confidence: 99%
“…The need to incise, resect, or retract the temporal or occipital lobes during surgery of the MTR is a controversial issue. 1,3,4,[8][9][10]12,13,15,20,26,27,29,30,33,[35][36][37][38][42][43][44][45][46][47][48]50,[57][58][59]67 This enclosed and extended localization near these highly significant structures renders the MTR a difficult surgical area in some respects. This location necessitates the least traumatic approach without the risk of injury to overlying…”
mentioning
confidence: 99%
“…Among them are the fusiform gyrus, left inferior frontal gyrus, and parahippocampal gyrus (Weis et al, 2004), the entorhinal cortex (Higuchi and Miyashita, 1996), and the anterior cingulate cortex (Frankland et al, 2004, Einarsson and Nader, 2012). Stimulation using subdural electrodes during object naming in patients with temporal lobe epilepsy (Mikuni et al, 2006) has demonstrated that two of these regions, i.e. the fusiform and parahippocampal gyri of the dominant hemisphere, belong to a basal temporal language area , which plays a role in both object naming and verbal memory.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, more selective resections have been performed to spare neocortical brain tissue not involved in epilepsy pathology. Subtemporal, transcortical, and transsylvian approaches are used for SAH . The rates of seizure freedom are reported to be between 62% and 78% in different series .…”
Section: Discussionmentioning
confidence: 99%